2016
DOI: 10.3389/fpls.2016.00566
|View full text |Cite|
|
Sign up to set email alerts
|

Orthology Analysis and In Vivo Complementation Studies to Elucidate the Role of DIR1 during Systemic Acquired Resistance in Arabidopsis thaliana and Cucumis sativus

Abstract: AtDIR1 (Defective in Induced Resistance1) is an acidic lipid transfer protein essential for systemic acquired resistance (SAR) in Arabidopsis thaliana. Upon SAR induction, DIR1 moves from locally infected to distant uninfected leaves to activate defense priming; however, a molecular function for DIR1 has not been elucidated. Bioinformatic analysis and in silico homology modeling identified putative AtDIR1 orthologs in crop species, revealing conserved protein motifs within and outside of DIR1’s central hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…The SAR is characterized by a lasting state of wide spectrum and is normally induced after HR [145], but can also be induced by PTI. Several potential SAR mobile signals have been identified [146]. Numerous studies have shown that DIR is essential for SAR [146149].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAR is characterized by a lasting state of wide spectrum and is normally induced after HR [145], but can also be induced by PTI. Several potential SAR mobile signals have been identified [146]. Numerous studies have shown that DIR is essential for SAR [146149].…”
Section: Resultsmentioning
confidence: 99%
“…Several potential SAR mobile signals have been identified [146]. Numerous studies have shown that DIR is essential for SAR [146149]. Among the DETs it stands out a DIR gene, suggesting induction of SAR in sugarcane infected by Aaa (S8 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Additional LTPs, like LTP1 and LTP2 and even AZELAIC ACID INDUCED1 (AZI1) and its homologs have a role in SAR signal development [ 54 , 55 ]. Moreover, DIR1 is conserved in other SAR-competent species like cucumber [ 56 ] and tobacco ( Nicotiana tabacum ) [ 57 ]. The lipid/acyl-CoA binding protein, ACBP6 is also required for SAR induction [ 58 ] and present in phloem exudates of SAR induced Arabidopsis plants [ 59 ].…”
Section: Multiple Signalling By Chemically Diverse Compounds Durinmentioning
confidence: 99%
“…DIR1 is a lipid transfer protein that has been shown to be phloem mobile during SAR and is required for systemic resistance [79,183]. While DIR1 alone does not induce resistance in distant tissues, it may be required for the transport of other SAR signals like DHA [131].…”
Section: Biotics Stress and Systemic Acquired Resistancementioning
confidence: 99%